Dermatitis artefacta: a challenging diagnosis - Giulia Ciccarese; Giorgia Salvia; Cristian Fidanzi; Mario Mastrolonardo; Francesco Drago (PAGEPress Publications, 2024)
Dear Editor, Dermatitis factitia (DF), also known as dermatitis artefacta, is a rare condition characterized by self-inflicted skin lesions. These lesions can be a result of compulsive habits driven by emotional distress, serving as a means of emotional release during episodes of anxiety or distress. Alternatively, they may be deliberately induced by the patient with the intention of gaining medical attention. DF is essentially the physical manifestation of underlying psychiatric disorders, making it a particularly challenging condition within the realm of medical practice. Being a diagnosis primarily based on the exclusion of an underlying disorder often requires multiple investigations that can impose a significant economic burden. [...]